Radical-Based Regioselective C-H Functionalization of Electron-Deficient Heteroarenes: Scope, Tunability, and Predictability - O'Hara, Fionn (2013)
Radical addition processes can be ideally suited for the direct functionalization of heteroaromatic bases, yet these processes are only sparsely used due to the perception of poor or unreliable control of regiochemistry. A systematic investigation of factors affecting the regiochemistry of radical functionalization of heterocycles using alkylsulfinate salts revealed that certain types of substituents exert consistent and additive effects on the regioselectivity of substitution. This allowed us to establish guidelines for predicting regioselectivity on complex π-deficient heteroarenes, including pyridines, pyrimidines, pyridazines and pyrazines. Since the relative contribution from opposing directing factors was dependent on solvent and pH, it was sometimes possible to tune the regiochemistry to a desired result by modifying reaction conditions. This methodology was applied to the direct, regioselective introduction of isopropyl groups into complex, biologically active molecules, such as diflufenican (44) and nevirapine (45).